Enhancing dynamic energy return and performance of running shoes: replacing talc with multi-walled carbon nanotubes derived from plastic wastes in midsole foam - Chang, Boon Peng (2024)
Boosting both the lightweight and rebound of a shoe's midsole without compromising its durability is regarded as a challenging aspect of developing excellent running shoes. This study explores the replacement of talc, a conventional reinforcing and nucleating agent for polymers, with multi-walled carbon nanotubes (MWCNTs) derived from plastics in the midsole foam of running shoes to enhance lightweight, rebound, and durability. Two types of MWCNTs, non-functionalized and oxygen-functionalized, derived from upcycling mixed plastics were processed with copolymer of ethyl-vinyl acetate (EVA) to create nanocomposite foams. The foam reinforced with non-functionalized MWCNTs exhibited higher dynamic stiffness and similar energy return to oxygen-functionalized MWCNTs. The running shoe prototypes with EVA midsole foam containing 0.5 wt% MWCNTs was 13 % lighter and returned more than 10 % higher energy than the conventional EVA midsole foam with mineral fillers. Additionally, the midsole foam produced from EVA/MWCNTs demonstrated greater flexibility, and durability after 500 km of dynamic impact cycles. The cost difference per pair of running shoe midsole is merely 0.08 USD, considering the exceptional performance of the EVA/MWCNTs midsole as compared to conventional mineral filled EVA midsole. These findings indicate the potential for commercializing EVA/MWCNTs nanocomposite foam as a viable option for high-performance running shoe midsoles, offering athletes improved running performance.